Did using input vouchers improve the distribution of subsidized fertilizer in Nigeria? The case of Kano and Taraba states - Liverpool-Tasie, Lenis Saweda O. (International Food Policy Research Institute, 2012)
Though input vouchers are increasingly being used as a mechanism to target subsidies in developing countries, limited empirical evidence of their performance relative to other distribution mechanisms exist. Consequently this study contributes to this scarce literature by comparing an input voucher program piloted in Nigeria in 2009 to the previous government led distribution mechanism. Input purchase experiences are compared when subsidized fertilizer was distributed through a voucher program or by the government. Using propensity score matching techniques, the study finds that voucher program participants received more bags of subsidized fertilizer than nonparticipants and paid a price significantly lower than the market price. However, they received their fertilizer later than nonparticipants and where significant had more underweight bags than nonparticipants. Given the costs associated with voucher programs, this study demonstrates when the distribution of subsidized fertilizer via vouchers improved farmers’ timely access to good and more affordable fertilizer.